Unveiling the Dynamics of the Omicron Variant: Prevalence, Risk Factors, and Vaccination Efficacy during the Third Wave of Covid-19 in Indonesia’s Gowa Regency - Amiruddin, Ridwan; Dwinata, Indra; Ayu, Rosa Devitha; Jafar, Nurhaedar; Gaffar, Gaffar; Kasim, Syaharuddin; Kasim, Muh Firdaus; Syarifah, Adriana (International Journal of Statistics in Medical Research, 2023)
Introduction: In February-March 2022, the B.1.1.529 (Omicron) variant of SARS-CoV-2 became the cause of the third wave of COVID-19 in Indonesia. However, data on the prevalence of the effects of the third wave of the COVID-19 pandemic are still limited, especially in regencies/cities in Indonesia. Gowa Regency is one of the most affected areas by COVID-19 in South Sulawesi. Objective: Ascertaining risk factors associated with infection and evaluating the effectiveness of vaccination programs in Gowa Regency. Methods: In March 2022, venous blood specimens were taken from 859 randomly selected samples in Gowa Regency to determine the presence of antibodies to SARS-CoV-2 by examining chemiluminescent microparticle immunoassay (CMIA) specimens. Information on demographics, previous infection history, symptoms, comorbid diseases, and vacancy status was collected through interviews. Data analysis was conducted using descriptive, bivariate tests with chi-square and One-way ANOVA, and multivariate tests using logistic regression. Results: The overall prevalence of anti-SARS-CoV-2-IgG was 98.7%. The results showed that the prevalence of SARS-CoV-2 antibodies was not significantly different in terms of sex (P=0.306), age group (P=0.190), education (P=0.749), and occupation (P=0.685), history of COVID-19 symptoms (P=0.108), history of confirmation of COVID-19 (P=0.352), and history of comorbid diseases (P=0.477). However, this study showed that the prevalence of SARS-CoV-2 antibodies differed significantly among the fully vaccinated and incomplete groups (P <0.001). Conclusion: There was a significant difference between the antibody status of respondents who had been fully vaccinated (at least two doses) and respondents who had not completed the vaccination.